2021
DOI: 10.3390/ani11041071
|View full text |Cite
|
Sign up to set email alerts
|

All Shades of Shrimp: Preferences of Colour Morphs of a Freshwater Shrimp Neocaridina davidi (Decapoda, Atyidae) for Substrata of Different Colouration

Abstract: An ornamental freshwater shrimp, Neocaridina davidi, is popular as an aquarium hobby and, therefore, a potentially invasive species. There is a growing need for proper management of this species to determine not only their optimum breeding conditions, but also their ability to colonise novel environments. We tested habitat preferences of colour morphs (brown, red, white) of N. davidi for substratum colour (black, white, grey shades, red) and fine or coarse chess-board patterns to recognise their suitable capti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Future experiments should focus on brightness and irradiance measured separately as significant variables (Moss et al, 1999). In another experiment, Plichta et al (2021) showed that Cherry shrimp ( Neocaridina davidi ) preferred darker backgrounds, regardless of carapace colouration. Suryanto et al (2023) demonstrated that Louisiana crawfish ( Procambarus clarkii ) preferred red and deterred yellow colour, whereas Australian red claw crayfish ( Cherax quadricarinatus ) preferred blue and deterred yellow colour again.…”
Section: Resultsmentioning
confidence: 97%
“…Future experiments should focus on brightness and irradiance measured separately as significant variables (Moss et al, 1999). In another experiment, Plichta et al (2021) showed that Cherry shrimp ( Neocaridina davidi ) preferred darker backgrounds, regardless of carapace colouration. Suryanto et al (2023) demonstrated that Louisiana crawfish ( Procambarus clarkii ) preferred red and deterred yellow colour, whereas Australian red claw crayfish ( Cherax quadricarinatus ) preferred blue and deterred yellow colour again.…”
Section: Resultsmentioning
confidence: 97%
“…Japanese freshwater shrimp(Neocaridina denticulata sinensis (Kemp 1918)) a species endemic to regions across Asia, ourish in diverse aquatic environments such as ponds, mountain streams, rivers, agricultural canals, and reservoirs (Nur and Christianus, 2013; Kenny et al, 2014;Plichta et al, 2021). The species' vibrant color variations and effective aquatic plant cleaning capacities have earned it signi cant popularity in the aquarium trade since its introduction around 2003 (Heerbrandt and Lin 2006;Nur and Christianus, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This gap in understanding has hindered progress in developing feeding strategies for crustaceans' early developmental stages, particularly given the growing demand and high market value of freshwater and marine aquaculture species and products. N. denticulata grows from a juvenile shrimp regime without undergoing a nauplius stage (Nur and Christianus, 2013;Plichta et al, 2021). Although it has a different growth mode than other crustaceans, it is an easy species to rear and a very good model to build upon.…”
Section: Introductionmentioning
confidence: 99%